Movement of PE Ratio and its Impact on Price Fluctuations: A Case Study of Dhaka Stock Exchange in Bangladesh (Global Journal of Management and Business Research, 2017)
This study describes the movement of PE ratio mentioned in corporate annual reports and impact on market price fluctuations in stock market. Specifically, this report discovers the affiliation between PE ratio and market price fluctuation in stock market in an emerging market like Dhaka stock Exchange, Bangladesh. For this purposes, it has analyzed and utilized a disclosure index about PE to measure the extent of relation with market fluctuation made by companies in corporate annual reports. This study reports that a very few company's share price in DSE are making efforts to run with PE ratio which are mostly quantitative in nature. Whether the price earnings ratio is a good criterion on which to base investment decisions is also examined in this report.
Keywords: price earnings ratio; price fluctuation; dhaka stock exchange; emerging market; earning per share